Analisis Kualitas Pelayanan Publik Di Kelurahan Cibeureum Kota Cimahi - Darilah Slopiatul Adawiyah; R Iim Takwim; H. Daros (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
Public service is an activity that involves at least two people, namely the party serving and the party being served. At this time it is said that service cannot be separated from human life because society always demands quality public services from an employee perspective, even though these demands are not in accordance with public expectations, the services that have occurred so far have been inaccurate or often late. This is indicated by the existence of various public complaints conveyed through the mass media, which can lead to an unfavorable image of government officials. Considering that the main function of the government is to serve the community, the government needs to strive to improve the quality of service. This study aims to determine and analyze the quality of public services in the Cibeureum Village, Cimahi City. This study uses qualitative research methods in a way that describes synergistic problems when the research is carried out. Data collection techniques are carried out by observation, interviews and documents. The instruments used in this study were observation sheets, interview sheets, and structured documentation made by the researchers themselves. The results showed that the quality of public services in the Cibeureum sub-district was in accordance with the existing terms and products, besides that public services in the Cibeureum sub-district had a fairly good level of timeliness and alertness so that people were enthusiastic enough to use public services.